On forecasting the time of incidence of Nor'westers at Calcutta - RAO , D. VENKATESWARA; BOOTHALINGAM, P. N. (MAUSAM, 1957)
The speed of travel of the downdrafts from regenerative Nor'wester sequences in southwest Bengal has been investigated by analysing data of times of their outbreak at Calcutta, Asansol and Hazaribagh. This is found to lie roughly between 30 and 40 mph. There are scarcely any thunder squalls at Calcutta before 1600 IST caused by parental storms at interior stations. Thunderstorms so generated are most frequent during 1700 to 1900 IST at Calcutta. The highest gust speeds in Nor'wester squalls also appear to be confined to this period. Thunderstorms occurring during 1100.1200 IST at Hazaribagh or 1400-1500 IST at Asansol produce squalls reaching 60-90 mph at Calcutta. From these results, simple rules for forecasting the time of incidence and speed likely to be attened in Nor'wester squalls at Calcutta have been deduced.